2016
DOI: 10.1177/0003489416674961
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo Secondary to Mild Head Trauma

Abstract: Benign paroxysmal positional vertigo associated with mild head trauma differs from idiopathic BPPV in terms of several epidemiological and clinical features; it responds less effectively to treatment and is prone to recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 30 publications
4
32
1
4
Order By: Relevance
“…The horizontal SCC BPPV has a prevalence exceeding 20% 49 of all cases in various reports, although according to other authors and in our own experience, its prevalence is quite lower, with a rate approaching 10%. 23 , 50 , 51 The frequency of anterior SCC involvement has been found, in some series, to be as high as 12%, 52 but according to our data and most of the relevant reports, its occurrence is much lower. 23 Anagnostou et al 53 in a systematic review estimated an occurrence of anterior SCC BPPV among patients with BPPV of 3% (range 1%–17.1%).…”
Section: Types Of Bppvsupporting
confidence: 50%
“…The horizontal SCC BPPV has a prevalence exceeding 20% 49 of all cases in various reports, although according to other authors and in our own experience, its prevalence is quite lower, with a rate approaching 10%. 23 , 50 , 51 The frequency of anterior SCC involvement has been found, in some series, to be as high as 12%, 52 but according to our data and most of the relevant reports, its occurrence is much lower. 23 Anagnostou et al 53 in a systematic review estimated an occurrence of anterior SCC BPPV among patients with BPPV of 3% (range 1%–17.1%).…”
Section: Types Of Bppvsupporting
confidence: 50%
“…In mixed-type vertigo, most prevalent combinations seen are posterior and horizontal canal pathologies, as was the case with our patient [1, 2, 4]. In a multicenter study presented by Leopardi et al, in only 4.4% of BPPV cases were multi-canal etiologies observed, and the authors reported combination of posterior and horizontal canal pathologies as most frequently seen type of BPPV [9].…”
Section: Discussionsupporting
confidence: 77%
“…In a series of 345 cases of BPPV reported by Balatsouras et al, only 32 cases had multi-canal etiology, and 11 of those occurred after a traumatic event [1]. They also detected viral etiologies and chronic otitis as underlying factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of secondary BPPV are: trauma (head trauma, whiplash), Meniere's disease, vestibular neuritis, sudden hearing loss, migraine headaches (basal and vestibular), ear surgery (stapedectomy, cochlear implantation), paranasal sinuses and dental surgeries and long-term immobilization. Head injuries have been estimated to be the most frequent cause of secondary BPPV and they account for 8.5-20% of all BPPV cases [5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%